Qualitative exploration of patient flow in a Caribbean emergency department - Steve Goodacre; Rachel O’Hara; Praveen Thokala; Seetharaman Hariharan; Loren De Freitas (BMJ Open)
Objectives Emergency departments (EDs) are complex adaptive systems and improving patient flow requires understanding how ED processes work. This study aimed to explore the patient flow process in an ED in Trinidad and Tobago, identifying organisational factors influencing patient flow.Methods Multiple qualitative methods, including non-participant observations, observational process mapping and informal conversational interviews were used to explore patient flow. The process maps were generated from the observational process mapping. Thematic analysis was used to analyse the data.Setting The study was conducted at a major tertiary level ED in Trinidad and Tobago.Participants Patient and staff journeys in the ED were directly observed.Results Six broad categories were identified: (1) ED organisational work processes, (2) ED design and layout, (3) material resources, (4) nursing staff levels, roles, skill mix and use, (5) non-clinical ED staff and (6) external clinical and non-clinical departments. Within each category there were individual factors that appeared to either facilitate or hinder patient flow. Organisational processes such as streaming, front loading of investigations and the transfer process were pre-existing strategies in the ED while staff actions to compensate for limitations with flow were more intuitive. A conceptual framework of factors influencing ED patient flow is also presented.Conclusion The knowledge gained may be used to strengthen the emergency care system in the local context. However, the study findings should be validated in other settings.